Security dilemmas of nuclear-armed Pakistan - Ahmed, Samina (2000)
Pakistan's security environment has deteriorated through its adoption of a declared nuclear weapons posture in May 1998. Internal fissures have widened along regional and sectarian lines as the Pakistani economy falters, unable to sustain even limited external sanctions following decades of internal mismanagement. Tensions with India have also increased as Pakistan's security managers adopt interventionist policies, based on a misplaced belief in the deterrent value of nuclear weapons. The international community, in particular, the USA's failure to reverse South Asian nuclear proliferation, has emboldened Indian advocates of nuclear deployment. If India deploys nuclear weapons and their delivery systems, Pakistan will follow suit. Operation-ready nuclear weapons will increase the prospects of an India-Pakistan conflict that could asume a nuclear dimension. :akistan's nuclear weapons capability will not prevent an Indian conventional attack nor will the presence of nuclear weapons deter an Indian accidental, unauthorised or preventive nuclear attack. Changed domestic and external priorities alone can buttress Pakistani security. - Reproduced
Keywords: State security